2014
DOI: 10.1186/s13047-014-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of seasonal variations in footwear worn by adults with inflammatory arthritis: a cross‐sectional observational study using a web‐based survey

Abstract: Background: Foot problems are common in adults with inflammatory arthritis and therapeutic footwear can be effective in managing arthritic foot problems. Accessing appropriate footwear has been identified as a major barrier, resulting in poor adherence to treatment plans involving footwear. Indeed, previous New Zealand based studies found that many people with rheumatoid arthritis and gout wore inappropriate footwear. However, these studies were conducted in a single teaching hospital during the New Zealand su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 51 publications
11
31
1
Order By: Relevance
“…We found that respondents expressed concern about the costs associated with appropriate footwear and the provision of foot care. This is an important finding in light of the results from the parent survey, in which 71% of respondents indicated that cost was important when choosing footwear . Previous studies demonstrate that arthritic conditions have a substantial impact on economic living standards .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We found that respondents expressed concern about the costs associated with appropriate footwear and the provision of foot care. This is an important finding in light of the results from the parent survey, in which 71% of respondents indicated that cost was important when choosing footwear . Previous studies demonstrate that arthritic conditions have a substantial impact on economic living standards .…”
Section: Discussionmentioning
confidence: 53%
“…This was a qualitative component of a larger national survey carried out in New Zealand collecting data on footwear experiences of people with chronic musculoskeletal diseases . The study sample was obtained from a population of Arthritis New Zealand members who were registered as having a chronic musculoskeletal disease.…”
Section: Methodsmentioning
confidence: 99%
“…Given a) the importance of offloading footwear and insert interventions, and b) the possibility that cultural commonalities may reduce adherence to closed footwear (particularly during the warm summer months [52]), further prospective research is required around footwear compliance in this population – since the efficacy of any offloading intervention among high-risk diabetic patients is entirely contingent on habitual adherence [32]. …”
Section: Discussionmentioning
confidence: 99%
“…Although New Zealand has a smaller general population than Australia, based on these existing published sample sizes [50,51], the current study survey response of PsA-speci c participants exceeded previous target samples by a substantial degree. Of the 43 participants who did not progress beyond the rst information page to enter the survey, a proportion may have been other researchers, health professionals and administrators promoting the study that previewed the online survey and inadvertently contributed to the number of non-completions.…”
Section: Discussionmentioning
confidence: 82%
“…The total target population was estimated from the major sites for dissemination to be 6000 people with PsA (10% response rate). Similar New Zealand-based podiatry surveys received 197 web-survey completions from people with in ammatory arthritis (49% response rate, n = 400 target sample) [50] and 131 postal survey completions (32% response rate, n = 400 target sample) were received from people with systemic lupus erythematous [51].…”
Section: Discussionmentioning
confidence: 99%